2009
DOI: 10.1073/pnas.0902348106
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic modeling methodology based on weighted Wiener chaos and Malliavin calculus

Abstract: In many stochastic partial differential equations (SPDEs) involving random coefficients, modeling the randomness by spatial white noise may lead to ill-posed problems. Here we consider an elliptic problem with spatial Gaussian coefficients and present a methodology that resolves this issue. It is based on stochastic convolution implemented via generalized Malliavin operators in conjunction with weighted Wiener spaces that ensure the ellipticity condition. We present theoretical and numerical results that demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…Such a difference between the Wick product and the regular product stems from the fact that the Wick product should be interpreted from the stochastic integral point of view. The connection of Wick product with Itô-Skorohod integral can be found in [7,11,9,18].…”
Section: Three Stochastic Elliptic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a difference between the Wick product and the regular product stems from the fact that the Wick product should be interpreted from the stochastic integral point of view. The connection of Wick product with Itô-Skorohod integral can be found in [7,11,9,18].…”
Section: Three Stochastic Elliptic Modelsmentioning
confidence: 99%
“…(27b) and (27c), the coefficients u II, a and u III, a can be solved one-by-one, which can be very efficient. We refer to [1,5,17,16,18,10] for more details about the accuracy and efficiency of the stochastic finite element methods for models (I) and (II). We subsequently summarize some theoretical results for models (I) and (II) with a(x, x) being a log-normal random process.…”
Section: Existence Of Solutionsmentioning
confidence: 99%
“…More specifically, using the lower triangular structure and the linearity of the uncertainty propagator and incorporating the estimates of the operator norms, we provide an a priori error estimate for the convergence of spectral/hp finite element method. For equations of stochastic order one, this analysis has been carried out in [22]. The same strategy can be replicated to obtain new a priori error estimates for other numerical methods for solving the propagator.…”
Section: Assumption a The Expectation Of The Highest Order (Differenmentioning
confidence: 99%
“…In fact, as we will see, the Wick propagator, i.e. the system of equations for the deterministic coefficients of the polynomial chaos expansion of the solution, is quasi-linear and sparse for Wick-type equations, including equations with polynomial Wick nonlinearities [6,9], Wick-multiplicative Gaussian noise [4,8,11], as well as noises represented by nonlinear transformations of Gaussian processes. By 'quasi-linear' here, we mean that only the equation for the mean field is nonlinear, whereas the rest of the system is linear, forming a hierarchy that can be readily solved.…”
Section: Introductionmentioning
confidence: 99%
“…This issue has been answered only partially in the past, for example, by Wan et al [8], where it was shown numerically that for elliptic SPDEs, the variance of the Wick solution was close to the stochastic solution for small perturbations but deviated greatly for large noise levels. Here, we revisit this issue and also study higher-order Wick-Malliavin approximations to the stochastic Burgers and NS equations.…”
Section: Introductionmentioning
confidence: 99%